Do the relationships of physical activity and total sleep time with cognitive function vary by age and biological sex? A cross-sectional analysis of the Canadian Longitudinal Study on Aging. (December 2022) - Falck, Ryan S.; Best, John R.; Barha, Cindy K.; Davis, Jennifer C.; Liu-Ambrose, Teresa
Highlights: Physical activity (PA) and total sleep time (TST) are associated with cognition. However, little is known about age and sex differences in these relationships. We examined age and sex differences in associations of PA and TST with cognition. PA is associated with better cognition irrespective of age and biological sex. TST has a complex relationship with cognition which is age and sex dependent. Abstract: Objectives: Physical activity (PA) and total sleep time (TST) are each associated with cognition; however, whether these relationships vary by age and biological sex is unclear. We examined the relationships of PA or TST with cognition, and whether age and sex moderated these relationships, using baseline data from the Canadian Longitudinal Study on Aging (CLSA; 2010–2015). Study design: A cross-sectional analysis of participants from the Comprehensive cohort of the CLSA with complete PA and sleep data (n = 20, 307; age range 45–86 years). Main outcome measures: PA and TST were measured using the Physical Activity Scale for the Elderly (PASE) and self-reported TST over the past month. Cognition was indexed using a three-factor structural equation model (i.e., memory, executive function, and verbal fluency). Results: Non-linear restricted cubic spline models indicated that PA and TST explained statistically significant (p < 0.01) but modest variance of each cognitive domain (<1 % of 23–24 % variance). Age and sex did not moderate associations of PA with any cognitive domain. However, age and sex moderated relationships of TST with cognition, whereby: 1) associations of TST with memory decreased with age for males and females; and 2) males and females had different age-associated relationships of TST with executive function and verbal fluency. Conclusions: PA and TST modestly contribute to multiple domains of cognition across middle and older adulthood. Importantly, the association of PA with cognition does not appear to vary across middle or older adulthood, nor does it vary by biological sex; however, TST appears to have a complex relationship with multiple domains of cognition which is both age- and sex-dependent.